Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466134
|View full text |Cite
|
Sign up to set email alerts
|

Stories of the Smartphone in everyday discourse

Abstract: As the smartphone proliferates in American society, so too do stories about its value and impact. In this paper we draw on advertisements and news articles to analyze cultural discourse about the smartphone. We highlight two common tropes: one calling for increased technological integration, the other urging individuals to dis-integrate the smartphone from daily life. We examine the idealized subject positions of these two stories and show how both simplistic tropes call on the same overarching values to compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 38 publications
0
83
1
5
Order By: Relevance
“…So just as multiple interpretations arise of the meaning of a single technology [28; 29], multiple interpretations of a single value arise, as well. This insight also builds on prior work suggesting how narratives of technology use in popular culture can portray alternative visions of the 'same' core value [11] by revealing how such tensions emerge in organizational functioning.…”
Section: Logics and The Interpretability Of Valuesmentioning
confidence: 66%
“…So just as multiple interpretations arise of the meaning of a single technology [28; 29], multiple interpretations of a single value arise, as well. This insight also builds on prior work suggesting how narratives of technology use in popular culture can portray alternative visions of the 'same' core value [11] by revealing how such tensions emerge in organizational functioning.…”
Section: Logics and The Interpretability Of Valuesmentioning
confidence: 66%
“…Mobile devices and their data connectivity have brought about new ways of being and doing, and images evoking these have made their way out of developed nations (where their use is most intense) across the world [9]. At each turn, HCI researchers and practitioners would do well to consider how we might move away from escalating data connectivity, and what genuine advantages this might also afford for quality of life [26].…”
Section: Resultsmentioning
confidence: 99%
“…(Bayer, Campbell, & Ling, 2016) developed a model to depict how societal norms and psychological perspectives influence the manner in which connection habits get triggered in everyday Mobile use. (Harmon & Mazmanian, 2013) identified that Mobile use at once triggers two contradictory discourses; of completely integrating technologically, becoming proficient in multi-tasking or becoming completely disintegrated from Mobile use in everyday life as it distracts and leads to addiction. However, the reality seems somewhere in between.…”
Section: Everyday Lifementioning
confidence: 99%